MON-236 Central Diabetes Insipidus in a Patient with Crohn’s Disease - Johns, Caroline Susan (J Endocr Soc, 2020)
Unusual Presentation of Central Diabetes Insipidus in a Patient with Crohn’s disease Introduction Autoimmune hypophysitis is defined as an inflammatory condition of the pituitary gland of autoimmune etiology that leads to pituitary dysfunction. There are three different histopathological categories of inflammatory hypophysitis including lymphocytic, granulomatous, and xanthomatous hypophysitis. Although, an autoimmune link has been suggested for lymphocytic hypophysitis (LH), the pathogenesis of autoimmune hypophysitis is still incompletely defined. The co-existence of LH and Crohn’s is a rare combination with only a few case reports in the literature. Case presentation We present a 39-year-old female with history of Crohn’s disease who presented to the ED with abdominal pain, poor oral intake and headaches. Lab work showed hypernatremia. A neck CT incidentally noted a nodular density along the superior aspect of the pituitary gland. A focused MRI of the pituitary showed abnormal thickening of the pituitary stalk with a prominent and heterogeneous gland. Endocrinology was consulted and on interview patient reported chronic headaches, polyuria and polydipsia for the past year, worsening over the past month. She denied any visual disturbances. Labs showed Na 159, K+ 4.0, serum osmolality 307, urine osmolality 178, specific gravity urine 1.006, cortisol 18, FSH 1.26, LH 0.12, prolactin 55, TSH 1.45 and free T4 0.84. Patient diagnosed with Diabetes Insipidus (DI) from LH and was started on PO desmopressin. Unfortunately, patient continued to have hypernatremia and increased urine output despite increases in the dose and frequency of the oral desmopressin. Given no clinical improvement, decision was made to switch from PO to IV desmopressin considering malabsorption of PO medication in the setting of Crohn’s disease. DI labs including plasma sodium, plasma osmolality, urine osmolality, specific gravity of urine and urine output were closely monitored. Patient’s hypernatremia and increased urine output started to improve with the switch to IV and was ultimately discharged home with intranasal desmopressin. Discussion Lymphocytic hypophysitis is a rare disorder predominantly affecting females during the antepartum or postpartum period. This case illustrates the importance of considering its presence in the setting of other autoimmune conditions. It also serves to illustrate the complex management and decision making followed in adjusting the desmopressin formulation in the setting of a malabsorptive disease such as Crohn’s.